(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article describes the results of studies on the selection of specific primers based on the rpoB gene of the causative agent of contagious goat pleuropneumonia (CBPP). For the selection of specific primers, NCBI resources were used: BLAST nucleotide and PRIMER BLAST. Primer synthesis was carried out by chemical preconcentration on a Synthesyzer H-16 device (K&A Laborgeraete). As a result of the work carried out, three pairs of primers for the rpoB gene were selected, satisfying in all respects.